Short Communication: The diversity of termites along the altitudinal gradient in a Karst Area of Southern Gombong, Central Java, Indonesia - Hery Pratiknyo; ENDANG ARIYANI SETYOWATI (Biodiversitas Journal of Biological Diversity, 2020)
Abstract. Pratiknyo H, Setyowati EA. 2020. Short Communication: The diversity of termites along the altitudinal gradient in a Karst Area of Southern Gombong, Central Java, Indonesia. Biodiversitas 21: 1730-1734. A karst area of Southern Gombong at altitudes of 0-500 m has a porous substrate whose soil content decreases as the altitude gets higher toward the top of the hill. This area is characterized by poor soil nutrient, but it has high CaCO3 and pH, which is not a favorable habitat for many species of termites which depend on soil substrate, as source of nutrient for community development, especially soil-feeding termites, as habitat for fungi as secondary daily diet, and as a stabilizer of the nest humidity. The aims of this research were to determine the diversity of termites along the altitudinal gradient in this karst area, and to determine the correlation between altitude and the termite diversity. The area was divided into 5 segments based on the altitudes, i.e., 0-100 m, 100-200 m, 200-300 m, 300-400 m, and 400-500 m. In each segment, a transect belt, 100 m long and 2 m wide, was made. Each transect was divided into 20 sections. Termites were sampled from living trees, branches, bark, litter and soil for 30 minutes per person in each section. The data were analyzed to determine the Shannon-Wienner diversity index (H¢), Shannon-Evenness index (E), and Simpson's Dominance index, and to find the correlation between the species diversity and altitude. The results showed that the termite diversity in the study site was low. Only four termite species were found with the indexes of diversity (H’), evenness (E), and dominance (D) of 1.01, 0.73 and 0.44 respectively. There was no linear correlation between termite diversity and altitude; the highest diversity was found in the middle altitudes, following the mid-domain effect model.